Institute of Information Sciences - research and coordinating center for the cobiss system in the Western Balkan region - Sokolova Irina (Наукові праці Національної бібліотеки України імені В.І. Вернадського)

(untitled)
The purpose of the article is to examine the activities and role of the Institute of Information Science of the Republic of Slovenia as a research center for the development and implementation of a structural and functional model of a library and information system in the countries of the Western Balkans region. The methodological basis of the research is based on the use of a complex of general scientific methods, in particular, analysis and synthesis, comparative analysis, generalization, and historical-systemic approach. Scientific novelty. The role and activity of the IZUM research institute as a center for supporting and coordinating the library and information system with corporate cataloging in the Western Balkans region, an electronic technological platform for the coordinated work of libraries, information infrastructure and services for the scientific sphere, which has not previously been covered in the Ukrainian librarianship literature. Conclusions. IZUM is a research centre that coordinates and ensures the interaction of all elements of the library and information system of the region, and conducts research in their field. The Institute carries out: performing the functions of the National COBISS Centre in Slovenia and coordinating the work of the National Centres in neighbouring countries; supporting the work of the electronic technology platform for interaction and communication between the libraries of the region; creating conditions for maintaining co-operative cataloging and common databases (COBIB, dCOBISS, E-CRIS, ADZ.Si, etc.); developing and implementing computer software standards, etc. The effectiveness and efficiency of cooperation between IZUM, libraries and scientific institutions have been tested by time and are highly valued at the international level, in particular by UNESCO. Acquaintance with the experience of building and functioning of the library and information system in the countries of the Western Balkans can be useful in developing conceptual foundations for the formation of national corporate information resources and increasing the efficiency of the Ukrainian library sphere. Adaptation of the experience of the library and information system with a research center can be implemented in similar Ukrainian network projects.